Resin beads, manufacturing method of resin beads, and products using resin beads
Resin beads with controlled crystallinity and hydrolyzed cellulose derivatives, combined with fillers, address the issues of aggregation and instability in natural alternatives, offering improved tactile sensation and skin compatibility in cosmetics and other products.
Patent Information
- Application Number
- JP2024007334
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2024-01-22
- Publication Date
- 2025-02-05
- Estimated Expiration
- 2044-01-22
AI Technical Summary
Conventional resin beads made from synthetic materials are contributing to marine pollution, and natural alternatives like powdered cellulose and cellulose derivatives suffer from aggregation, texture issues, and instability when blended into cosmetics, leading to poor skin feel and product stability.
Development of resin beads containing cellulose with controlled crystallinity, hydrolyzed cellulose derivatives, and specific particle sizes, along with fillers and additives, to enhance touch and skin compatibility, using a method involving suspension polymerization and hydrolysis to form spherical beads with a smooth surface.
The resulting resin beads provide excellent tactile sensation and skin growth, improving the texture of cosmetics and other products while being biodegradable and environmentally friendly.
Smart Images

Figure 0007627368000001 
Figure 0007627368000002 
Figure 0007627368000003
Abstract
Description
[Technical field]
[0001] The present invention relates to resin beads, a method for producing the resin beads, and products obtained using the resin beads. [Background technology]
[0002] Conventionally, resin beads have been used in various fields such as matting agents, slipping agents, and antiblocking agents due to their spherical properties. Furthermore, various resin powders (resin particles) such as resin beads are used to improve the properties of makeup cosmetics such as spreadability. However, in recent years, due to problems such as marine pollution caused by microplastics, the constituent materials of resin beads incorporated into cosmetics are shifting from synthetic materials derived from petroleum to natural materials.
[0003] As spherical resin particles made of natural materials, for example, powdered cellulose useful as a scrubbing agent has been proposed (Patent Document 1). Furthermore, cellulose derivative fine particles used in diagnostic agents (Patent Document 2) and spherical cellulose powder used in cosmetics (Patent Documents 3 and 4) have been proposed. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2018-052909 A [Patent Document 2] International Publication No. 2009 / 123148 [Patent Document 3] JP 2013-221000 A [Patent Document 4] Patent No. 7134542 Summary of the Invention [Problem to be solved by the invention]
[0005] However, the particle size of the powdered cellulose etc. proposed in Patent Document 1 was not suitable for incorporation into makeup or skin care cosmetics. In addition, the cellulose derivative fine particles proposed in Patent Document 2 require the use of cuprammonium during production, and therefore are not necessarily suitable as a material for cosmetics in which heavy metals should be reduced as much as possible.
[0006] Furthermore, the spherical cellulose powders and the like proposed in Patent Documents 3 and 4 have high cohesiveness, and even when incorporated into cosmetics, they do not spread well on the skin, and tend to feel rough. In addition, their texture is prone to change significantly when they are wetted or incorporated into a solution. For this reason, when incorporated into cosmetics, the cosmetics themselves tend to become unstable, and therefore they are not necessarily suitable as materials for cosmetics.
[0007] The present invention has been made in consideration of the problems of the conventional technology, and an object of the present invention is to provide resin beads which can be substituted for resin particles made of synthetic materials derived from petroleum and which can provide various products such as cosmetics having excellent touch and spreadability on the skin, and various products such as cosmetics using the same. Another object of the present invention is to provide a method for producing resin beads which can be substituted for resin particles made of synthetic materials derived from petroleum and which can provide various products such as cosmetics having excellent touch and spreadability on the skin. [Means for solving the problem]
[0008] That is, according to the present invention, there are provided the following resin beads. [1] Resin beads comprising a filler and a resin portion encapsulating the filler, the resin portion containing cellulose having a crystallinity of 50% or less as calculated by the following formula (1): Crystallinity (%)={(AB) / A}×100 (1) A: The peak intensity of the diffraction peak at a diffraction angle of 2θ = 21.8° ± 0.3° measured by X-ray diffraction using Cu-Kα radiation as an X-ray source. B: Peak intensity of the diffraction peak at a diffraction angle of 2θ = 15.0° ± 0.3° measured by X-ray diffraction using Cu-Kα radiation as an X-ray source. [2] The resin beads according to [1], wherein the cellulose is a hydrolysate of a cellulose derivative. [3] The resin beads according to [2], wherein the cellulose derivative is a cellulose ester. [4] The resin beads according to any one of [1] to [3], wherein the average particle size of the filler is 2 μm or less. [5] The resin beads according to any one of [1] to [4], wherein the filler is at least one selected from the group consisting of inorganic particles and pigments. [6] The resin beads according to any one of [1] to [4], wherein the filler is at least one selected from the group consisting of metal salts and metal oxides. [7] The resin beads described in [6], wherein the metal salt is at least one selected from the group consisting of barium sulfate and calcium carbonate, and the metal oxide is at least one selected from the group consisting of titanium oxide, zinc oxide, and aluminum oxide.
[0009] Furthermore, according to the present invention, there is provided a method for producing resin beads as described below. [8] A method for producing resin beads according to any one of [1] to [7] above, comprising the steps of: mixing an oil phase containing a filler, a cellulose derivative, and an organic solvent that dissolves the cellulose derivative and has a solubility of 0.1 to 50.0 g in 100 g of water at 25°C with an aqueous phase containing a dispersion stabilizer to prepare a suspension containing oil droplets containing the filler, the cellulose derivative, and the organic solvent; removing the organic solvent from the oil droplets in the suspension to form resin particles containing the filler and the cellulose derivative; and hydrolyzing the cellulose derivative in the resin particles to form cellulose. [9] The method for producing resin beads according to [8], comprising adding water to the suspension, removing the organic solvent from the oil droplets in the suspension, and shrinking the oil droplets to form the resin particles.
[0010] Further, according to the present invention, there are provided the following products:
[10] A product comprising resin beads, which is any one of a cosmetic, a dermatological drug, a paint, a molded body, a film, a coating agent, and a resin composition, wherein the resin beads are the resin beads described in any one of [1] to [7] above. Effect of the Invention
[0011] According to the present invention, it is possible to provide resin beads that can be substituted for resin particles made of synthetic materials derived from petroleum, which can provide various products such as cosmetics having excellent touch and spreadability on the skin, and various products such as cosmetics using the same. Also, according to the present invention, it is possible to provide a manufacturing method for resin beads that can be substituted for resin particles made of synthetic materials derived from petroleum, which can provide various products such as cosmetics having excellent touch and spreadability on the skin. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] Hereinafter, the embodiments of the present invention will be described, but the present invention is not limited to the following embodiments. Note that various physical property values in this specification are values at room temperature (25° C.) unless otherwise specified.
[0013] The present inventors have conducted various studies on highly biodegradable resin beads made of natural materials, which can provide various products such as cosmetics that have excellent tactile sensation and spreadability on the skin, and on methods for producing the same. As a result, it has been found that resin beads made mainly of natural materials and capable of providing various products such as cosmetics that have the above-mentioned various properties can be obtained by using the following configuration. That is, one embodiment of the resin beads of the present invention has a filler and a resin part that encapsulates the filler. The resin part contains cellulose having a crystallinity of 50% or less, calculated by the following formula (1). It is preferable that the resin part is substantially formed only from cellulose having a crystallinity of 50% or less, calculated by the following formula (1). Crystallinity (%)={(AB) / A}×100 (1) A: The peak intensity of the diffraction peak at a diffraction angle of 2θ = 21.8° ± 0.3° measured by X-ray diffraction using Cu-Kα radiation as an X-ray source. B: Peak intensity of the diffraction peak at a diffraction angle of 2θ = 15.0° ± 0.3° measured by X-ray diffraction using Cu-Kα radiation as an X-ray source.
[0014] Cellulose is usually composed of crystalline and amorphous parts, and exhibits various functions as a material that supports plants. To utilize such functions, natural cellulose itself may be used directly, cellulose derivatives obtained by chemically changing the structure of natural cellulose may be used, or chemically regenerated regenerated cellulose may be used. Known crystalline forms of cellulose include natural cellulose type I and regenerated cellulose type II. The diffraction peaks of regenerated cellulose type II measured by X-ray diffraction are located at diffraction angles 2θ ≒ 12°, 20°, and 22°. The shape and intensity of each diffraction peak differ depending on the manufacturing method of the regenerated cellulose.
[0015] The crystallinity of the cellulose (cellulose II type crystals) contained in the resin part constituting the resin beads of this embodiment is 50% or less, preferably 40% or less, and more preferably 30% or less. The substantial lower limit of the crystallinity is 0°. By setting the crystallinity of the cellulose constituting the resin part to the above range, the crystallinity and cohesiveness of the resin part can be alleviated. Therefore, by using resin beads having a resin part containing cellulose whose crystallinity is within the above range, various products such as cosmetics having excellent touch and spreadability on the skin can be provided.
[0016] If the crystallinity of the cellulose is too high, the resin portion becomes tough and hard, and the tendency to aggregate during drying increases, making it difficult to pulverize, and the yield may decrease due to the need for classification. Also, if the crystallinity of the cellulose is too high, the resin beads will not roll easily, the smoothness will decrease, and the texture will become rough and significantly deteriorated.
[0017] The X-ray diffraction peaks of cellulose can be measured using a commercially available X-ray diffraction device (for example, the product name "Miniflex600" (manufactured by RIGAKU)). Specifically, finely ground resin beads (resin part containing cellulose) are pressed against a holder, and the measurement is performed by scanning at a diffraction angle 2θ of 5 to 30°. The X-ray source used is Cu-Kα radiation (40 kV, 15 mA) monochromatized with a Kβ filter.
[0018] The crystallinity of cellulose can be calculated from the above formula (1) using the peak intensity (A) of the diffraction peak at a diffraction angle 2θ=21.8°±0.3° corresponding to the crystalline and amorphous parts, and the peak intensity (B) of the diffraction peak at a diffraction angle 2θ=15.0°±0.3° corresponding to the amorphous part. When the crystallinity calculated from the above formula (1) is negative (-), the crystallinity is set to 0%.
[0019] The cellulose contained in the resin part is preferably a hydrolysate of a cellulose derivative. The resin part may contain cellulose and a cellulose derivative. From the viewpoint of enhancing the biodegradability of the resin beads, the content of cellulose in the resin part is preferably 50 to 100% by mass, more preferably 60 to 100% by mass, and particularly preferably 70 to 100% by mass. In other words, the resin part is preferably substantially composed of cellulose alone.
[0020] The cellulose contained in the resin portion may be blended in advance into the resin portion from the beginning of the production of the resin beads, or may be produced by chemically modifying a cellulose derivative during the production process of the resin beads. The crystalline type of the cellulose blended in advance into the resin portion may be either type I or type II.
[0021] The cellulose derivative is a modified cellulose having three hydroxyl groups in one unit. The cellulose derivative may be one in which one hydroxyl group in one unit is modified, two hydroxyl groups in one unit is modified, or three hydroxyl groups in one unit is modified. The structure of the group modifying the hydroxyl group may be any of linear, branched, and cyclic. The cellulose derivative may also be a salt.
[0022] As the cellulose derivative, a known cellulose derivative can be appropriately selected and used, taking into consideration the purpose of use of the resin beads, etc. Examples of the cellulose derivative include methyl cellulose, ethyl cellulose, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, nitrocellulose, hydroxypropyl methylcellulose, hydroxyethyl methylcellulose, hydroxypropyl cellulose, hydroxypropyl methylcellulose phthalate, hypromellose acetate succinate, carboxymethyl cellulose, and cellulose glycolate ether. Examples of the cellulose acetate include acetyl cellulose, diacetyl cellulose, and triacetyl cellulose.
[0023] The cellulose derivative is preferably a cellulose ester that is used in cosmetics and other products as a natural cellulose derivative. Examples of the cellulose ester include cellulose fatty acid ester, cellulose organic acid ester, and cellulose phosphate ester. Among them, the cellulose ester is preferably at least one selected from the group consisting of cellulose acetate, cellulose propionate, cellulose acetate propionate, cellulose butyrate, and cellulose acetate butyrate.
[0024] The cumulative 50% particle size of resin beads by volume (median diameter; D 50 ) is preferably 50 μm or less, more preferably 30 μm or less, particularly preferably 0.1 to 30 μm, and most preferably 0.5 to 20 μm.50 By setting the range above, it is possible to more effectively exhibit the slipperiness required for resin beads to be blended in cosmetics and the like.
[0025] Cumulative 90% particle size (D 90 The cumulative 10% particle diameter (D) of the resin beads based on volume is preferably 40 μm or less, and more preferably 5 to 25 μm. 10 ) is preferably 0.1 μm or more, and more preferably 1.5 to 10 μm. The CV value (coefficient of variation) of the particle diameter of the resin beads is preferably 10 to 90%. 90 , D 10 By setting the CV value within the above ranges, it is possible to more effectively achieve the smoothness without a foreign body sensation required for resin beads to be blended into cosmetics and the like, and to obtain cosmetics in which penetration into wrinkles is suppressed. 50 ), cumulative 10% particle size by volume (D 10 ), and cumulative 90% particle size (D 90 ) can be measured using a Coulter counter (Beckman Coulter).
[0026] The sphericity of the resin beads is preferably 0.5 or more and 1.0 or less, more preferably 0.6 to 1.0 or less, and particularly preferably 0.7 to 1.0 or less. By setting the sphericity within the above range, it is possible to effectively achieve the good tactile feel and spreadability on the skin required for resin beads blended in cosmetics and the like.
[0027] The sphericity, which is an index of whether a resin bead is spherical or not, can be measured and calculated according to the following procedure. First, an SEM image of the resin bead taken with a scanning electron microscope (SEM) is subjected to image analysis, and the circularity C of each resin bead is calculated according to the following formula (2). Then, the arithmetic mean value of the circularities C of 10 or more arbitrarily selected resin beads is taken as the sphericity. C = (4πS1) / (L 2 ) ···(2)
[0028] In the above formula (2), S1 represents the area (projected area) of the resin bead in the image, and L represents the length of the outer periphery of the resin bead in the image. The closer the circularity C value is to 1, the closer the particle shape is to a perfect sphere.
[0029] The surface smoothness of the resin beads is preferably 50 to 100%, more preferably 60 to 100%, and particularly preferably 70 to 100%. By keeping the surface smoothness within the above range, it is possible to effectively achieve the good tactile feel and spreadability on the skin required for resin beads to be blended in cosmetics and the like.
[0030] The surface smoothness of resin beads can be measured according to the following procedure. That is, an SEM image (x5,000) of the resin beads taken with a scanning electron microscope (SEM) is observed, and the smoothness M of each resin bead is calculated according to the following formula (3). The arithmetic mean value of the smoothness M of 10 or more arbitrarily selected resin beads is then taken as the surface smoothness. The closer the smoothness M value is to 1, the smoother the particle surface is. M=(1-(S3) / (S2))×100 ···(3)
[0031] In the above formula (3), S2 indicates the area (projected area) of the resin bead in the image, and S3 indicates the sum of the area formed by the outline of the resin particle when the resin bead is superimposed on a circle that approximates it, and the area inside and outside the outline of the superimposed circle.
[0032] The solidity of the resin beads is preferably 50 to 100% by volume, more preferably 60 to 100% by volume, and particularly preferably 70 to 99% by volume. By setting the solidity within the above range, the low oil absorption required for the resin beads to be blended in cosmetics and the like can be effectively achieved. If the solidity of the resin beads is less than 50% by volume, the oil absorption tends to be high. For this reason, when resin beads with a low solidity are blended in a product such as a cosmetic, the viscosity of the cosmetic may increase, and the stability of the product may be easily reduced.
[0033] The solidity of resin beads can be measured and calculated according to the following procedure. First, a scanning electron microscope (SEM) image of the cross section of a resin bead is analyzed, and the volume of the resin part and the part filled with filler of each resin bead is calculated. Then, the average value of the volumes of the resin part and the part filled with filler of 10 or more randomly selected resin beads is taken as the solidity (volume %).
[0034] The 5-day biodegradability of the resin beads is preferably 20% or more, more preferably 30% or more, and particularly preferably 40% or more. By setting the biodegradability of the resin portion within the above range, it is possible to achieve the good biodegradability required for the resin beads to be blended in cosmetics and the like.
[0035] The 5-day biodegradation rate of the resin part of the resin beads is measured in accordance with JIS K6950:2000 (ISO 14851:1999). More specifically, the 5-day biodegradation rate of the resin beads is measured and calculated by testing under the following conditions (BOD measurement using a closed oxygen consumption measuring device). Inoculum source: Aerobic reactor sludge from sewage treatment plants that mainly treat domestic wastewater Control material: microcrystalline cellulose Test substance concentration: 100mg / L Control substance concentration: 100mg / L Inoculum concentration: 150mg / L Test liquid volume: 300mL Test temperature: 25±1℃ Culture period: 30 days
[0036] The biodegradation rates of the test substance and the reference substance can be calculated from the following formula. Biodegradation rate (%)=(BODO-BODB) / ThOD×100 BODO (mg): Biochemical oxygen demand of the test substance BODB (mg): Average biochemical oxygen demand of the control material ThOD (mg): The theoretical maximum amount of oxygen required to oxidize the test substance
[0037] The resin beads have a filler and a resin portion that encapsulates the filler. That is, the resin beads encapsulate the filler. In a mixture in which the filler is not encapsulated in the resin portion and the filler and the resin are simply mixed, the filler's specific properties such as poor slipperiness, powderiness, and hardness become apparent, and therefore, even if the filler is added to a cosmetic product, it cannot effectively express the tactile sensation and spreadability on the skin. In this specification, the state of "encapsulating the filler" means either a state in which the entire surface of each filler is covered with the resin portion, or a state in which only a portion of the surface of each filler is covered with the resin portion.
[0038] Average particle size of the filler (cumulative 50% particle size by volume (median size; D 50 )) is preferably 2 μm or less, more preferably 1.5 μm or less, and particularly preferably 1 μm or less. 50 The lower limit of the filler is not particularly limited, and it is sufficient if it is 0.01 μm or more. 50 Considering the particle size of the resin beads, the D of the filler relative to the resin beads can be adjusted within the range of inclusion. 50 If D is too large, it may be difficult to include the filler. 50 If the particle size is too small, the dispersibility is likely to decrease, and the viscosity of the raw material may be likely to increase excessively during the production of the resin beads. This may make it difficult to produce resin beads with the desired particle size. 50 ) can be measured using a Coulter counter (Beckman Coulter).
[0039] The filler inclusion rate of the resin beads is preferably 98% or less, more preferably 97% or less, and particularly preferably 95% or less. The lower limit of the filler inclusion rate is not particularly limited, and it is sufficient that it is substantially 0.1% or more. The filler inclusion rate may be appropriately adjusted so that the crystallinity of cellulose and the like are within the desired range. The state in which the filler is inclusion in the resin beads can be confirmed, for example, by observation using an optical microscope or a scanning electron microscope (SEM) or image analysis. The filler inclusion rate of the resin beads is the ratio (%) of the mass of the filler to the total mass of the filler and the resin part.
[0040] Examples of the filler include glass, polymers, fibers, magnetic materials, metal powders, inorganic particles, pigments, and cellulose fibers. Among them, the filler is preferably at least one selected from the group consisting of inorganic particles and pigments. Known inorganic particles and pigments can be used. Examples of the inorganic particles and pigments include carbon black, titanates, magnetic materials, ferrites, iron powder, iron oxide, boron nitride, mica, talc, kaolin, aluminum powder, aluminum hydroxide, magnesium hydroxide, alumina, carbon black, and legal Japanese names for dyes such as Yellow No. 4, Red No. 202, and Blue No. 1. The inorganic particles and pigments may be surface-treated with at least one selected from the group consisting of silicone, fatty acids, fatty acid metal salts, amino acids, amino acid metal salts, oils and fats, and lipids.
[0041] The filler is preferably at least one selected from the group consisting of metal salts and metal oxides. Known metal salts and metal oxides can be used. Examples of metal salts and metal oxides include titanium oxide, zinc oxide, red iron oxide, yellow iron oxide, black iron oxide, titanium oxide, zinc oxide, aluminum oxide, barium sulfate, and calcium carbonate. Among these, aluminum oxide, barium sulfate, calcium carbonate, titanium oxide, and zinc oxide are preferred, and barium sulfate is more preferred.
[0042] When the resin beads of this embodiment are manufactured by the manufacturing method described later, the crystallinity of the cellulose contained in the resin part to be formed can be reduced by including a filler. The reason why the crystallinity of the cellulose is reduced by including a filler is not necessarily clear, but the present inventor speculates as follows. In the manufacturing method described later, an oil phase containing a filler, a cellulose derivative, and a predetermined organic solvent is prepared. In this oil phase, a state is formed in which the filler is adsorbed or electrically close to the polar part of the cellulose derivative, and then resin particles containing the filler and the cellulose derivative are formed. Thereafter, when the cellulose derivative is hydrolyzed to form cellulose, it is considered that the filler adsorbed or close to the polar part of the cellulose derivative inhibits the crystallization or crystal growth of cellulose, and the crystallinity of cellulose is reduced.
[0043] It is presumed that inorganic particles and pigments interact more strongly with cellulose derivatives. Therefore, from the viewpoint of further reducing the crystallinity of the cellulose forming the resin portion, it is preferable to use at least one selected from the group consisting of inorganic particles and pigments as a filler. In addition, among inorganic particles and pigments, it is preferable to use at least one selected from the group consisting of metal salts and metal oxides as a filler, and it is more preferable to use aluminum oxide, barium sulfate, calcium carbonate, titanium oxide, zinc oxide, etc., and it is particularly preferable to use barium sulfate.
[0044] The resin part constituting the resin beads may further contain components such as a surfactant, a dispersant, and a polymer dispersant. In addition, the resin part constituting the resin beads may contain at least one of an ultraviolet absorbing agent and an ultraviolet scattering agent depending on the application. To obtain resin beads having a resin part containing an ultraviolet absorbing agent or an ultraviolet scattering agent, for example, a suspension may be prepared using an oil phase further containing at least one of an ultraviolet absorbing agent and an ultraviolet scattering agent. Examples of ultraviolet absorbing agents include fine titanium dioxide particles, fine zinc oxide particles, cinnamic acid-based ultraviolet absorbing agents, and dibenzoylmethane-based ultraviolet absorbing agents.
[0045] The resin beads may be surface-treated with silicone, fatty acid, fatty acid metal salt, amino acid, amino acid metal salt, oil, fat, lipid, or the like depending on the application.
[0046] Next, a method for producing the above-mentioned resin beads will be described. One embodiment of the method for producing resin beads of the present invention is the method for producing the above-mentioned resin beads, and includes a suspension preparation step, a granulation step, and a hydrolysis step. The suspension preparation step is a step of preparing a suspension containing oil droplets containing a filler, a cellulose derivative, and an organic solvent having a solubility of 0.1 to 50.0 g in 100 g of water at 25°C, which dissolves the filler, a cellulose derivative, and an aqueous phase containing a dispersion stabilizer, by mixing the oil phase. The granulation step is a step of removing the organic solvent from the oil droplets in the suspension obtained in the suspension preparation step to form resin particles containing the filler and the cellulose derivative. And the hydrolysis step is a step of hydrolyzing (saponifying) the cellulose derivative in the resin particles formed in the granulation step to form cellulose, thereby generating the desired resin beads.
[0047] In the suspension preparation process, an oil phase containing a filler, a cellulose derivative, and an organic solvent that dissolves the cellulose derivative is mixed with an aqueous phase containing a dispersion stabilizer. By mixing the oil phase and the aqueous phase and stirring as necessary, a suspension in which oil droplets containing a cellulose ester and an organic solvent are dispersed in water can be obtained. Since the oil droplets are present in a dispersed state in water, the organic solvent in the oil droplets gradually moves into the water. Then, the oil droplets shrink with the movement of the organic solvent, and the cellulose derivative dissolved in the organic solvent gradually precipitates while covering the filler. The precipitated cellulose derivative grows while encapsulating the filler and maintaining a smooth surface. Finally, the precipitated cellulose derivative is fixed, and resin particles that are precursors of resin beads are formed. Whether or not the oil droplets have shrunk can be determined by analyzing images observed using an optical microscope, an electron microscope, or the like. By shrinking the oil droplets in this way, resin beads of the desired particle size can be obtained that have high sphericity (sphericity), high solidity, and a smooth surface.
[0048] The cellulose derivative may be any of the above-mentioned cellulose derivatives, including cellulose ester. By hydrolyzing at least a part of the ester bonds in the cellulose ester in the hydrolysis step described below, it is possible to maintain physical properties suitable for cosmetic applications, such as the feel and spreadability on the skin. In other words, by selecting the hydrolysis conditions, it is possible to suppress problems that occur when cellulose is produced, and to obtain resin beads that can be suitably incorporated into cosmetics and the like.
[0049] As the cellulose ester, it is preferable to use a cellulose ester having an acyl group content of 60% by mass or less, such as an acetyl group, a propionyl group, or a butyroyl group. In particular, it is preferable to use a cellulose acetate or a cellulose acetate propionate having an acyl group content of 60% by mass or less. It is also preferable to use a cellulose ester having a viscosity of 200 mPa·s or less in a 6% by mass acetone solution. When these cellulose esters are used, defects in the particle size distribution and the touch of the resulting resin beads are unlikely to occur, and it is possible to more easily obtain resin beads that can be suitably incorporated into cosmetics and the like.
[0050] As the cellulose derivative, a commercially available cellulose derivative may be used as it is, or the cellulose derivative may be used after being hydrolyzed or esterified according to a conventional method to adjust the acyl group content. Furthermore, a plurality of resin beads having different acyl groups may be mixed to control the acyl group content of the entire resin beads to be within a predetermined range.
[0051] As the organic solvent (first organic solvent) contained in the oil phase, a known organic solvent capable of dissolving a cellulose derivative can be used. Specific examples of the organic solvent include ester-based solvents such as methyl formate, ethyl formate, methyl acetate, ethyl acetate, and butyl acetate; ketone-based solvents such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone; alcohols such as ethanol and n-butanol; ether-based solvents such as ethyl cellosolve, butyl cellosolve, and ethylene glycol diethyl ether; glycol ether-based solvents such as dipropylene glycol monomethyl ether; glycol ester-based solvents such as propylene glycol monomethyl ether acetate; chlorine-based solvents such as methylene chloride, chloroform, and tetrachloroethane; nitromethane; propylene carbonate, etc. These organic solvents can be used alone or in combination of two or more.
[0052] As the organic solvent, ketone-based solvents, ester-based solvents, alcohols, glycols, ether-based solvents, alkyl halides, and alkyl nitrates are preferred, and among these, methyl ethyl ketone, ethyl acetate, butanol, propylene glycol monobutyl ether, propyl acetate, and propylene glycol monomethyl ether acetate are more preferred.
[0053] If the water solubility of the organic solvent in the oil droplets contained in the suspension is too high, the organic solvent will be easily transferred from the oil droplets to the water phase during suspension, so that the resin beads formed by the shrinkage of the oil droplets may not be spherical or may not have a smooth surface. If the water solubility of the organic solvent is too low, the organic solvent may be easily left in the resin beads. For this reason, the solubility of the organic solvent in 100 g of water (water solubility) at 25°C is 0.1 to 50.0 g, preferably 0.5 to 40.0 g, and more preferably 1.0 to 30.0 g.
[0054] The amount of the organic solvent contained in the oil phase (first liquid) is preferably 2.0 times or more, more preferably 2.5 to 15.0 times, by mass, the amount of the cellulose derivative. If the amount of the organic solvent in the oil phase is too small, the cellulose derivative is likely to precipitate rapidly when the organic solvent is removed from the oil droplets in the suspension in the particulation step described below. For this reason, the obtained resin beads may be difficult to form a perfect sphere or a smooth surface.
[0055] The aqueous phase used in the suspension preparation step is a liquid (second liquid) in which a dispersion stabilizer is dissolved in water such as deionized water. Examples of the dispersion stabilizer that can be used include water-soluble polymers such as water-soluble cellulose, polyvinyl alcohol, and sodium polyacrylate; and inorganic salts such as hydroxyapatite, calcium triphosphate, and calcium carbonate. These dispersion stabilizers can be used alone or in combination of two or more. Among these dispersion stabilizers, it is preferable to use water-soluble polymers such as water-soluble cellulose, polyvinyl alcohol, and sodium polyacrylate.
[0056] In order to prevent the oil droplets in the suspension from being destroyed or coalesced during transportation, it is preferable to appropriately set the type and concentration of the dispersion stabilizer used in the aqueous phase. The content of the dispersion stabilizer in the aqueous phase is preferably 30% by mass or less, and more preferably 1 to 20% by mass.
[0057] The aqueous phase preferably further contains a second organic solvent. The organic solvent in the oil phase (first organic solvent) may rapidly move to the aqueous phase depending on its type. Therefore, by mixing the aqueous phase containing the second organic solvent with the oil phase, it is possible to suppress the rapid movement of the first organic solvent in the oil phase to the aqueous phase, and resin beads with higher sphericity and smoother surface can be produced. As the second organic solvent, the same organic solvent as the above-mentioned organic solvent (first organic solvent) used in the oil phase, including suitable ones, can be used. The first organic solvent and the second organic solvent may be the same or different.
[0058] In the suspension preparation step, the oil phase and the aqueous phase are mixed to prepare a suspension. To mix the oil phase and the aqueous phase, the oil phase may be added to the aqueous phase under stirring, or the aqueous phase may be added to the oil phase under stirring. The suspension may be in a state where oil droplets are dispersed in the aqueous phase (O / W), or may be in a state where water droplets are dispersed in the oil phase (W / O) and then phase-inverted to a state where oil droplets are dispersed in the aqueous phase (O / W). If necessary, it is preferable to use an emulsifying device such as a disperser or homogenizer to adjust the particle size of the formed oil droplets. For example, the particle size of the formed oil droplets can be easily adjusted by changing the rotation speed of the homogenizer to adjust the shear force. As a result, the particle size of the obtained resin beads can be appropriately adjusted to be within the desired range.
[0059] The amount of the aqueous phase is preferably 3.0 times or less, more preferably 0.2 to 2.8 times, by mass, the amount of the oil phase. By setting the amount of the aqueous phase within the above range, it is possible to suppress the rapid migration of the organic solvent in the oil droplets to the aqueous phase, and it is possible to produce resin beads with higher sphericity and smoother surfaces.
[0060] In the granulation step, the organic solvent is removed from the oil droplets in the suspension obtained in the suspension preparation step. This allows the formation of resin particles containing a filler and a cellulose derivative. As a method for removing the organic solvent from the oil droplets in the suspension and precipitating the cellulose derivative to form resin particles, for example, there is a method for distilling off the organic solvent by heating the suspension to a temperature equal to or higher than the azeotropic point of the organic solvent and water. By further reducing the pressure, the organic solvent can be distilled off at a temperature lower than the azeotropic point. It is also preferable to adjust the degree of reduction in pressure and distill off the organic solvent at a temperature closer to room temperature.
[0061] It is also preferable to add water to the suspension, remove the organic solvent from the oil droplets in the suspension, and shrink the oil droplets to form resin particles. By adding water to the suspension, the organic solvent in the oil droplets can be transferred to the aqueous phase, and cellulose derivative particles can be precipitated. This allows the oil droplets in the suspension to be rapidly shrunk, and resin particles and resin beads with higher sphericity and smoother surfaces can be produced. The amount of water added to the suspension is preferably 0.1 times or more, and more preferably 1 to 100 times, the amount of the suspension by mass. To remove the organic solvent from the oil droplets in the suspension and precipitate the cellulose derivative to form resin particles, a method of adding water to the suspension to shrink the oil droplets and a method of heating the suspension under reduced pressure to distill off the organic solvent may be combined. The particulation step is preferably carried out at a temperature as close to room temperature as possible.
[0062] In the hydrolysis step, the cellulose derivative in the resin particles formed in the granulation step is hydrolyzed (saponified) to form cellulose. This allows the production of the desired resin beads in which the filler is encapsulated in the resin portion containing the desired cellulose.
[0063] Cellulose derivatives such as cellulose esters can be hydrolyzed under acidic or alkaline conditions. The pH during hydrolysis under alkaline conditions is preferably 13.5 or less, more preferably 9.0 to 13.0. The temperature during hydrolysis is preferably 70°C or less, more preferably 60°C or less, and particularly preferably 0 to 50°C. If the temperature during hydrolysis exceeds 70°C, the hydrolysis may proceed excessively, and the crystallinity of cellulose may increase. This may cause the resin part formed to be hard and easily aggregated. On the other hand, by setting the temperature during hydrolysis to 70°C or less, resin beads having a better touch and stretchability on the skin that can be suitably blended in cosmetics and the like can be obtained. The degree of hydrolysis (degree of progress) can be monitored at any time by infrared spectroscopy (IR). After the degree of hydrolysis (degree of progress) is confirmed, an acid or alkali may be added to neutralize it.
[0064] After hydrolysis, for example, the resulting resin beads are filtered and washed to remove unnecessary components. Next, washing is repeated multiple times as necessary, followed by drying and crushing to obtain the desired resin beads. After crushing, a comb treatment may be performed to remove coarse particles, and a yield of 95% or more is sufficient with a 300 mesh (opening of about 45 μm), preferably 97% or more, and more preferably 98% or more. If necessary, the particle size may be adjusted by classification or the like. Furthermore, if necessary, the resin particles may be surface-treated by a conventional method using silicone, fatty acid, fatty acid metal salt, amino acid, amino acid metal salt, oil and fat, lipid, etc.
[0065] The resin beads of this embodiment reduce the crystallinity of the cellulose contained in the resin portion, thereby suppressing the particles from becoming hard due to tough crystals and reducing the cohesion. Therefore, the resin beads of this embodiment can effectively express the excellent touch and spread on the skin required for resin beads to be blended in cosmetics, etc. By containing the resin beads of this embodiment, various products such as cosmetics, dermatological drugs, paints, molded bodies, films, coating agents, and resin compositions that are provided with excellent touch, spread on the skin, and product stability can be provided without using resin particles made of synthetic materials derived from petroleum. EXAMPLES
[0066] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. In the examples and comparative examples, "parts" and "%" are by mass unless otherwise specified.
[0067] <Production of resin beads> Example 1 A cellulose acetate solution was prepared by dissolving 168.3 parts of cellulose acetate (trade name "CA-398-3", Eastman Chemical Co., acetyl group content: 39.8%) in 1125.4 parts of ethyl acetate (water solubility: 8 g / 100 g). In addition, 58 parts of cellulose acetate (trade name "CA-398-3", Eastman Chemical Co., acetyl group content: 39.8%) was dissolved in 852 parts of ethyl acetate, and then 390 parts of barium sulfate (Sakai Chemical Industry Co., Ltd., average particle size 0.5 μm) were mixed and dispersed to prepare a dispersion. Then, 150.5 parts of the prepared dispersion and the cellulose acetate solution were mixed to prepare an oil phase. In addition, 40 parts of polyvinyl alcohol were dissolved in 760 parts of ion-exchanged water to prepare an aqueous phase. The oil phase was added to the prepared aqueous phase, mixed, and stirred using a dissolver to obtain a suspension in which oil droplets were uniformly dispersed.
[0068] While stirring the suspension obtained using a dissolver, 22,500 parts of ion-exchanged water was injected over 30 minutes to obtain a resin particle dispersion (resin bead dispersion). The resin particles were filtered and washed, then peptized in ion-exchanged water and stirred. The resin particles obtained by filtration and washing were dispersed in ion-exchanged water. After heating to 40°C, caustic soda was added so that the pH was 13.5 or less to perform a hydrolysis reaction. After the completion of the hydrolysis reaction, the mixture was neutralized with hydrochloric acid, and the product was filtered and washed, and then peptized in ion-exchanged water. After filtering, washing, and drying, the mixture was crushed to obtain resin beads. The obtained resin beads were observed and image-analyzed using a scanning electron microscope (SEM), and it was confirmed that the filler (barium sulfate) was encapsulated in the resin portion. In the following, it was confirmed that the filler was encapsulated in the resin portion in the same manner. The peak intensity of the diffraction peak at a diffraction angle of 2θ=21.8° of the obtained resin beads (resin part) measured using an X-ray diffractometer (product name "Miniflex600" (manufactured by RIGAKU Corporation), X-ray source: Cu-Kα radiation (40 kV, 15 mA)) was 9,901 cps. The peak intensity of the diffraction peak at a diffraction angle of 2θ=15.0° was 7,684 cps, and the crystallinity of the resin beads (resin part) calculated by formula (1) was 22.4%. The crystallinity of the resin beads (resin part) was calculated in the same manner.
[0069] Example 2 A cellulose acetate solution was prepared by dissolving 113.8 parts of cellulose acetate (trade name "CA-398-3", Eastman Chemical Co., acetyl group content: 39.8%) in 796.4 parts of ethyl acetate. In addition, 58 parts of cellulose acetate (trade name "CA-398-3", Eastman Chemical Co., acetyl group content: 39.8%) was dissolved in 852 parts of ethyl acetate, and then 390 parts of barium sulfate (Sakai Chemical Industry Co., Ltd., average particle size 0.8 μm) were mixed and dispersed to prepare a dispersion. Then, 250.7 parts of the prepared dispersion and the cellulose acetate solution were mixed to prepare an oil phase. In addition, 36 parts of polyvinyl alcohol were dissolved in 564 parts of ion-exchanged water to prepare an aqueous phase. The oil phase was added to the prepared aqueous phase, mixed, and stirred using a dissolver to obtain a suspension in which oil droplets were uniformly dispersed.
[0070] While stirring the obtained suspension using a dissolver, 20,000 parts of ion-exchanged water was poured in over 30 minutes to obtain a resin particle dispersion (resin bead dispersion). The resin particles were filtered and washed, then peptized in ion-exchanged water and stirred. The resin particles obtained by filtration and washing were dispersed in ion-exchanged water. After heating to 40°C, caustic soda was added to adjust the pH to 13.5 or less to perform a hydrolysis reaction. After completion of the hydrolysis reaction, the mixture was neutralized with hydrochloric acid, and the product was filtered and washed, then peptized in ion-exchanged water. After filtration, washing, and drying, the mixture was crushed to obtain resin beads. The crystallinity of the obtained resin beads (resin portion) is shown in Table 1.
[0071] Example 3 A cellulose acetate solution was prepared by dissolving 25.4 parts of cellulose acetate (trade name "CA-398-3", Eastman Chemical Co., acetyl group content: 39.8%) in 206.5 parts of ethyl acetate. In addition, 58 parts of cellulose acetate (trade name "CA-398-3", Eastman Chemical Co., acetyl group content: 39.8%) was dissolved in 852 parts of ethyl acetate, and then 390 parts of barium sulfate (Takehara Chemical Co., Ltd., average particle size 1.0 μm) was mixed and dispersed to prepare a dispersion. Then, 351.3 parts of the prepared dispersion and the cellulose acetate solution were mixed to prepare an oil phase. In addition, 18 parts of polyvinyl alcohol were dissolved in 282 parts of ion-exchanged water to prepare an aqueous phase. The oil phase was added to the prepared aqueous phase, mixed, and stirred using a dissolver to obtain a suspension in which oil droplets were uniformly dispersed.
[0072] While stirring the obtained suspension using a dissolver, 9,000 parts of ion-exchanged water was poured in over 30 minutes to obtain a resin particle dispersion (resin bead dispersion). The resin particles were filtered and washed, then peptized in ion-exchanged water and stirred. The resin particles obtained by filtration and washing were dispersed in ion-exchanged water. After heating to 30°C, caustic soda was added to adjust the pH to 13.5 or less to perform a hydrolysis reaction. After completion of the hydrolysis reaction, the mixture was neutralized with hydrochloric acid, and the product was filtered and washed, then peptized in ion-exchanged water. After filtration, washing, and drying, the mixture was crushed to obtain resin beads. The crystallinity of the obtained resin beads (resin portion) is shown in Table 1.
[0073] Example 4 A cellulose acetate solution was prepared by dissolving 168.3 parts of cellulose acetate (trade name "CA-398-3", Eastman Chemical Co., acetyl group content: 39.8%) in 1125.4 parts of ethyl acetate. In addition, 58 parts of cellulose acetate (trade name "CA-398-3", Eastman Chemical Co., acetyl group content: 39.8%) was dissolved in 852 parts of ethyl acetate, and then 390 parts of alumina (Nikkeikin Co., Ltd., average particle size 1.7 μm) were mixed and dispersed to prepare a dispersion. Then, 150.5 parts of the prepared dispersion and the cellulose acetate solution were mixed to prepare an oil phase. In addition, 40 parts of polyvinyl alcohol were dissolved in 760 parts of ion-exchanged water to prepare an aqueous phase. The oil phase was added to the prepared aqueous phase, mixed, and stirred using a dissolver to obtain a suspension in which oil droplets were uniformly dispersed.
[0074] The suspension obtained was heated to 50°C while stirring using a dissolver, and the pressure was reduced while maintaining the temperature to distill off ethyl acetate, obtaining a resin particle dispersion (resin bead dispersion). The resin particles were filtered and washed, then peptized in ion-exchanged water and stirred. The resin particles obtained by filtration and washing were dispersed in ion-exchanged water. After heating to 50°C, caustic soda was added to adjust the pH to 13.5 or less to perform a hydrolysis reaction. After completion of the hydrolysis reaction, the mixture was neutralized with hydrochloric acid, and the product was filtered and washed, then peptized in ion-exchanged water. After filtration, washing, and drying, the mixture was crushed to obtain resin beads. The crystallinity of the obtained resin beads (resin portion) is shown in Table 1.
[0075] Comparative Example 1 Commercially available cellulose fine particles (product name "CELLULOBEADS D-10", manufactured by Daito Kasei Co., Ltd.) were used as the resin beads in Comparative Example 1. The crystallinity of the resin beads is shown in Table 1.
[0076] Comparative Example 2 An oil phase was prepared by dissolving 250 parts of cellulose acetate (trade name "CA-398-3", Eastman Chemical Co., acetyl group content: 39.8%) in 2,250 parts of ethyl acetate. An aqueous phase was prepared by dissolving 50 parts of polyvinyl alcohol in 1,200 parts of ion-exchanged water. The oil phase was added to the prepared aqueous phase and mixed, and the mixture was stirred using a dissolver to obtain a suspension in which oil droplets were uniformly dispersed.
[0077] While stirring the obtained suspension using a dissolver, 45,000 parts of ion-exchanged water was poured in over 30 minutes to obtain a resin particle dispersion (resin bead dispersion). The resin particles were filtered and washed, then peptized in ion-exchanged water and stirred. The resin particles obtained by filtration and washing were dispersed in ion-exchanged water. After heating to 50°C, caustic soda was added to adjust the pH to 13.5 or less to perform a hydrolysis reaction. After completion of the hydrolysis reaction, the mixture was neutralized with hydrochloric acid, and the product was filtered and washed, then peptized in ion-exchanged water. After filtration, washing, and drying, the mixture was crushed to obtain resin beads. The crystallinity of the obtained resin beads is shown in Table 1.
[0078] <Evaluation of resin beads> (Average particle size) The average particle diameter of the resin beads (cumulative 50% particle diameter on a volume basis (median diameter; D)) was measured using a Coulter counter (Beckman Coulter, Inc.). 50 The results are shown in Table 1.
[0079] (Inclusion rate) The inclusion rate of the filler was calculated according to the following method in accordance with JIS K 5101-15-2:2004. The sample was placed in a dryer maintained at a temperature of 105±2°C and dried for 2 hours, then allowed to cool to room temperature in a desiccator. Approximately 2 g of the cooled sample was placed in a ceramic crucible previously adjusted to a constant weight, and the mass was measured to the nearest 0.1 mg. The sample was gradually heated using a gas burner or electric furnace so as not to scatter. After there was nothing to burn, the sample was ignited at 600°C for approximately 1 hour. The ignited ceramic crucible was placed in a desiccator and allowed to cool to room temperature, and the mass was measured to the nearest 0.1 mg. The mass measured after ignition was divided by the mass of the sample before heating to calculate the inclusion rate of the filler. The results are shown in Table 1.
[0080] TIFF0007627368000001.tif63170
[0081] (Tactile sensation) A sensory evaluation was conducted by a panel of 10 people regarding the feel of the resin beads. They touched the resin beads and made a comprehensive judgment on "smoothness" and "ease of spreading on the skin," and rated them on a 5-point scale according to the following evaluation criteria, and the average score of the 10 people was calculated. The results are shown in Table 2. 5: Good 4: Fairly good 3: Normal 2: Somewhat bad 1: Bad
[0082] TIFF0007627368000002.tif55170
[0083] <Production of cosmetics> (Cosmetics-1) Cosmetic-1 was produced by mixing various ingredients conventionally used as raw materials for cosmetics. Specifically, first, each silicone-treated powder (mica, talc, and fine titanium oxide particles) and each resin bead were mixed in the amounts shown in Table 3 and mixed until uniform to obtain a powder mixture. Next, a mixture (other ingredients) obtained by mixing Vaseline, squalane, and glyceryl trioctanoate was added to the powder mixture and mixed until uniform, then filled into a container and press-molded as necessary to obtain cosmetic-1.
[0084] TIFF0007627368000003.tif71170
[0085] (Cosmetics-2) Various ingredients conventionally used as raw materials for cosmetics were mixed to produce cosmetic preparation-2, which is a sun-cut emulsion. Specifically, first, silicone oil, UV protection agent, emulsifier, dispersant, isotridecyl isononanoate, and each resin bead were mixed in the amounts shown in Table 4 to prepare an oil phase component. In addition, purified water, dipropylene glycol, sodium chloride, and sodium citrate were mixed in the amounts shown in Table 4 to prepare an aqueous phase component. Next, the aqueous phase component was added to the prepared oil phase component while stirring to emulsify, and cosmetic preparation-2 was obtained.
[0086] TIFF0007627368000004.tif90170
[0087] <Evaluation of Cosmetic-1> (Touch, spread on skin) A sensory evaluation was conducted by a panel of 10 people on the texture and spreadability of cosmetic preparation-1 on the skin. The "good texture" and "spreadability on the skin" were judged and scored out of 5 according to the following evaluation criteria, and the average score of the 10 people was calculated. The results are shown in Table 5. 5: Good 4: Fairly good 3: Normal 2: Somewhat bad 1: Bad
[0088] TIFF0007627368000005.tif57170
[0089] <Evaluation of Cosmetic-2> (Touch, spread on skin) A sensory evaluation was conducted by a panel of 10 people on the texture and spreadability of cosmetic preparation-2 on the skin. The "good texture" and "spreadability on the skin" were judged and scored out of 5 according to the following evaluation criteria, and the average score of the 10 people was calculated. The results are shown in Table 6. 5: Good 4: Fairly good 3: Normal 2: Somewhat bad 1: Bad
[0090] TIFF0007627368000006.tif55170
[0091] As shown in Tables 5 and 6, it is understood that the use of the resin beads of the Examples enabled the production of cosmetics with excellent touch and spreadability on the skin. It was also confirmed that the use of the resin beads of the Examples enabled the imparting of properties such as excellent touch and spreadability not only to cosmetics but also to various products such as dermatological drugs, paints, molded bodies, films, coating agents, and resin compositions. [Industrial Applicability]
[0092] The resin beads of the present invention have properties equal to or greater than those of resin beads formed from synthetic materials derived from petroleum. Therefore, by using the resin beads of the present invention, it is possible to provide products such as cosmetics that have a good feel and spread well on the skin, even without using resin beads formed from synthetic materials derived from petroleum. Therefore, the resin beads of the present invention are useful as a constituent material for various products such as cosmetics, skin care products, paints, molded bodies, films, coating agents, and resin compositions.
Claims
1. A filler (excluding those treated with at least one selected from the group consisting of silicone, fatty acid, fatty acid metal salt, amino acid, amino acid metal salt, oil and fat, and lipid) and a resin part containing the filler, The resin portion comprises cellulose having a crystallinity of 50% or less, as calculated by the following formula (1): Crystallinity (%) = {(AB) / A}×100 (1) A: Peak intensity of the diffraction peak at a diffraction angle 2θ = 21.8 ° ± 0.3 ° measured by X-ray diffraction using Cu-Kα rays as an X-ray source B: Peak intensity of the diffraction peak at a diffraction angle 2θ = 15.0° ± 0.3° measured by X-ray diffraction using Cu-Kα radiation as an X-ray source
2. 2. The resin beads according to claim 1, wherein the cellulose is a hydrolysate of a cellulose derivative.
3. 3. The resin beads according to claim 2, wherein the cellulose derivative is a cellulose ester.
4. 2. The resin beads according to claim 1, wherein the average particle size of the filler is 2 μm or less.
5. 2. The resin beads according to claim 1, wherein the filler is at least one selected from the group consisting of inorganic particles and pigments.
6. 2. The resin beads according to claim 1, wherein the filler is at least one selected from the group consisting of metal salts and metal oxides.
7. The metal salt is at least one selected from the group consisting of barium sulfate and calcium carbonate, 7. The resin beads according to claim 6, wherein the metal oxide is at least one selected from the group consisting of titanium oxide, zinc oxide, and aluminum oxide.
8. A method for producing the resin beads according to any one of claims 1 to 7, comprising the steps of: a step of mixing an oil phase containing a filler (excluding those treated with at least one selected from the group consisting of silicone, fatty acid, fatty acid metal salt, amino acid, amino acid metal salt, oil and fat, and lipid), a cellulose derivative, and an organic solvent capable of dissolving the cellulose derivative and having a solubility of 0.1 to 50.0 g in 100 g of water at 25° C., with an aqueous phase containing a dispersion stabilizer to prepare a suspension containing oil droplets containing the filler, the cellulose derivative, and the organic solvent; removing the organic solvent from the oil droplets in the suspension to form resin particles containing the filler and the cellulose derivative; hydrolyzing the cellulose derivative in the resin particles to form cellulose; A method for producing resin beads having the formula:
9. The method for producing resin beads according to claim 8, further comprising the steps of: adding water to the suspension; removing the organic solvent from the oil droplets in the suspension; and shrinking the oil droplets to form the resin particles.
10. A product comprising resin beads, which is any one of a cosmetic, a dermatological drug, a paint, a molded body, a film, a coating agent, and a resin composition, A product, wherein the resin beads are the resin beads according to any one of claims 1 to 7.
Citation Information
Patent Citations
Amorphous cellulose fine powder
JP2004331918A
Particle including colored inorganic pigment and makeup cosmetic containing inorganic pigment
JP2005139127A
Pigment-containing cellulose powder and cosmetic, resin and coating containing the same
JP2007056086A
Black-colored spherical cellulose powder and cosmetic
JP2007211131A
Method for producing cellulose particle
JP2010155982A